HUBUNGAN ANTARA KARAKTERISTIK ANGGOTA DAN DINAMIKA KELOMPOK DENGAN EFEKTIVITAS PROGRAM PEKARANGAN PANGAN LESTARI (P2L) PADA KWT MEKAR LESTARI KOTA SALATIGA - Rinory, Armandho; Prihtanti, Tinjung Mary (Universitas Sebelas Maret, 2022)
This study aims to analyze the relationship between member characteristics and group dynamics with the effectiveness of a sustainable food garden program. The selection of research locations was conducted deliberately (purposive), namely at KWT Mekar Lestari, Randuacir Subdistrict Argomulyo Salatiga City. This study uses a type of descriptive research quantifiable with survey methods sampling techniques using saturated sampling or census with 30 samples or all KWT Mekar Lestari members. Data collection techniques are carried out using questionnaires, and variable dynamics of groups measured by Likert scale techniques tested validity and reliability. Data analysis techniques used descriptive statistical and Spearman Rank correlation. The results showed that age, education, and membership status had an insignificant relationship with a deficient level of relationship with the effectiveness of the P2L program. Group dynamics seen from its elements, namely group goals, group structure, group cohesiveness, group atmosphere, and group effectiveness have a significant relationship with the level of a strong relationship with the effectiveness of the P2L program, while group task functions and group coaching and maintenance have a moderate relationship and significant with the effectiveness of the P2L program. The element of group pressure has a deficient and insignificant relationship with the effectiveness of the P2L program.